Rhombohedral ZnIn2S4-catalysed anodic direct electrochemical oxidative cleavage of C–O bond in α-O-4 linkages in ambient conditions - Zhu, Qi; Gong, Bo; Huang, Shuquan; Jin, Yangxin; Liu, Shengqin; Shao, Shan; Yang, Yuwei; Taren Cataldo; Bedford, Nicholas M; Jason Chun-Ho Lam (Green chemistry : an international journal and green chemistry resource : GC, 2024)
The electrochemical selective oxidative transformation of lignin feedstocks into valuable oxygenated aromatics is essential to establish a sustainable biorefinery. In this study, we used a rhombohedral ZnIn2S4 (R-ZIS) electrocatalyst to realise the efficient anodic cleavage of C–O bonds in benzyl phenyl ether (BPE), an α-O-4 lignin model compound, to a series of industrially relevant oxygenated mono-aromatics. The reaction occurred at +2 VAg/AgCl, 65 °C, and atmospheric pressure. In optimised conditions, the reaction achieved over 99% conversion rate with a Faraday efficiency of 51.6% at 91.3% conversion of BPE, that is greater than most known electrocatalytic oxidative cleavage examples. The ZnIn2S4 electrocatalyst was deposited on a carbon cloth support, and its structural properties and surface morphology were extensively investigated. Systematic potential controlled electrolysis coupled with 18O isotopic labelling confirmed that C–O scission occurred exclusively between the benzylic carbon and phenolic oxygen. Furthermore, substrate competition studies were conducted to compare the electrocatalytic performance of the R-ZIS catalyst with that of its structural analogue, hexagonal ZnIn2S4, in terms of BPE and mono-aromatics conversion. The experimental results were supported by density functional theory calculations. The substrate scoping study revealed the suitability of the R-ZIS induced electrocatalytic system for a variety of substituted α-O-4/β-O-4 model dimers. Overall, this work demonstrates an efficient anodic process that can enable the atom-efficient valorisation of lignin to produce oxygenated aromatics. The proposed approach can complement the numerous existing reductive lignin cleavage methods.